El modelado y la motricidad fina en los adultos mayores del “hogar de ancianos y aislamiento Riobamba” en el año 2016 - Llivicota Peñafiel, Jessica Lorena (2017)
This research project aims to develop the fine motor skills of the older adult of the home of Elderly and Isolation of the city of Riobamba, by applying different basic modeling techniques such as: macaroni or churros technique, pellet or ball, pressure, plates, punching, shoveling, stamping, and technique of painting applied on the clay, which will favor the improvement of fine motor skills. Through the manipulation of the clay psychomotor aspects are developed both to regenerate the movement of the hands and to encourage creativity. This activity is important as it also helps in their emotional well-being, is a means of socialization and resource of infinite possibilities for the development of fine motor skills. The realization of a field study through the technique of observation to obtain the best results to test the hypothesis. After the application of the mentioned instruments it was possible to verify that excellent results were obtained because it was possible to improve the concentration, the creativity, the socialization and the expression in general. The scientific, analytical synthetic methods contributed to analyze each presented, descriptive and practical situation favored the work mentioned, for the processing of data in the verification of the hypothesis statistical studies were used that helped to conclude that the creation is important of an artistic workshop where they can continue working with clay and other materials that are manipulated so that in this way they do not lose in their totality the functionality of their hands and there for retain their driving capacity.